Floristic diversity and rare components of feather-grass steppes in the Mokra Sura river basin (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Feather-grass steppes in the Mokra Sura river basin was studied. Species lists are compiled for four formations of genus Stipa L. with 209 species from 126 genera and 36 families. A list of rare and endangered species is compiled as well with giving conservational status to all 28 species.
Keywords: feather-grass formations, Mokra Sura, rare species.